Gender Differences in Automatic In -Group Bias Why Do Women Like Women Than Men Like Men? (article). - Rudman, Laurie A.
Four experiments confirmed that women's automatic in-group bias is remarkably stronger m than men's and investigated explanations for this sex difference, derived from potential sources of implicit attitudes (L. R. Rudman, 2004). In experiment 1, only women (not men) showed cognitive balance among in-group bias, identify, and self-esteem (A. G. Greenwald et al, 2002), revealing that men lack a mechanism that bolsters automatic group preference. Experiments 2-- (from the author) and 3 found pro-female bias to the extent that participants automatically favored their mothers over their fathers of associated male gender with violence, suggesting that maternal bonding and male intimidation influence gender attitudes . Experiment 4 showed that for sexually experienced men, the more positive their attitude was toward sex, the more they implicitly favored women. In concert the findings help to explain sex differences in automatic in-group bias and underscore the uniqueness of gender for inter group relations theorists. -- (from the author).
Keywords: Psychology-Periodicals.